2019
DOI: 10.3390/insects10010033
|View full text |Cite|
|
Sign up to set email alerts
|

Ecological Drivers of Species Distributions and Niche Overlap for Three Subterranean Termite Species in the Southern Appalachian Mountains, USA

Abstract: In both managed and unmanaged forests, termites are functionally important members of the dead-wood-associated (saproxylic) insect community. However, little is known about regional-scale environmental drivers of geographic distributions of termite species, and how these environmental factors impact co-occurrence among congeneric species. Here we focus on the southern Appalachian Mountains—a well-known center of endemism for forest biota—and use Ecological Niche Modeling (ENM) to examine the distributions of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…Accordingly, if high precipitation was important for facilitating range expansion, these conditions seem to have been in place at a time that coincides with colonization of the central region. Furthermore, seasonal differences in precipitation between the southern and northern portions of the study region (Hyseni & Garrick, 2019) This contrast supports the view that fine-scale genetic structuring may be particularly prevalent in topographically complex montane areas (Garrick, 2011;Hedin & Wood, 2002;Thomas & Hedin, 2008).…”
Section: The Potential Role Of Environmental Variables In Promotingsupporting
confidence: 79%
See 1 more Smart Citation
“…Accordingly, if high precipitation was important for facilitating range expansion, these conditions seem to have been in place at a time that coincides with colonization of the central region. Furthermore, seasonal differences in precipitation between the southern and northern portions of the study region (Hyseni & Garrick, 2019) This contrast supports the view that fine-scale genetic structuring may be particularly prevalent in topographically complex montane areas (Garrick, 2011;Hedin & Wood, 2002;Thomas & Hedin, 2008).…”
Section: The Potential Role Of Environmental Variables In Promotingsupporting
confidence: 79%
“…Accordingly, if high precipitation was important for facilitating range expansion, these conditions seem to have been in place at a time that coincides with colonization of the central region. Furthermore, seasonal differences in precipitation between the southern and northern portions of the study region (Hyseni & Garrick, ) may have led to different flight phenologies and thus seasonal isolation and niche partitioning. Consistent with this, dbRDA revealed that in addition to spatial structuring of genetic variation, wet‐season precipitation accounted for the remainder of genetic differentiation of the Southern cluster compared to the other two.…”
Section: Discussionmentioning
confidence: 99%
“…The first impression that comes to our mind about termites is the considerable damage they cause to man-made wooden structures and agronomic and forest resources [9], which is globally estimated to cost around USD 40 billion [10]. Few however are informed about the many benefits derivable from termites and their termitaria which can be sustainably managed to human advantage.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently come to our attention that two of the environmental rasters we used for analyses in our study [1] were mislabeled in a raster processing pipeline. As a result, in the article [1], all references to dry-season precipitation and summer temperature require switching. Here, Figures 1 and 2 and Table 1, are the corrected versions of Figures 1 and 3 and Table 2 in the article [1].…”
mentioning
confidence: 99%
“…As a result, in the article [1], all references to dry-season precipitation and summer temperature require switching. Here, Figures 1 and 2 and Table 1, are the corrected versions of Figures 1 and 3 and Table 2 in the article [1].…”
mentioning
confidence: 99%